The Correlation Between Family And School Condition Toward Student English Achievement At Class Viii Smpn 02 Sungaipua Academic Year 2019/2020 - ASP, Verdana Islami; Syahrul; Melanni, Melyan (The Explora, 2025)
The research aims to know: (1) The relationship of family conditions to learning achievements; (2) The relationship of the school condition to learning achievement; and (3) the relationship of family conditions and the school conditions jointly to the learning achievement of class VIII SMPN 02 Sungaipua academic year 2019/2020. The subject of this research is all students of grade VIII SMPN 02 Sungaipua, amounting to 24 students who were entirely taken as research respondents. The results showed that condition of the family and school had positively influential in the study of English language studies. This indicates that when family and school conditions are increased, student learning achievements will also increase. Results of multiple regression analyses obtained the equation Y = 8,242 + 0. 051 X1 + 0. 365 X2. A partial test (T-Test) obtained T compute variable influence family's condition = 6.607 so that Ha X1 to Y was acceptable. Variable influence of school condition acquired t count = 3,019, so that Ha X2 against Y was acceptable. The effective donation of family conditions was 21,316%, the school's condition was 39,678%.